: soil; nutrientes; forage; NPK. BENEFITS OF NPK FERTILIZATION IN PASTURES AND BOVINE PRODUCTIVITY (REMUNOM, 2024)
Cattle farming is an important activity in rural Brazil, both from an economic and social perspective, as it employs many people in production and throughout its agri-food chain. It also supplies nutritious food and by-products to the Brazilian and international markets, contributing to improving food security and the trade balance. Pasture plays an important role in providing animals with high-quality daily forage that meets their nutritional needs in an economical way. The present study has the general objective of evaluating the performance of nitrogen, phosphorus and potassium fertilization, presenting the following specific objectives: to understand the importance of weed control, the use of appropriate forages and the use of fertilizers for better pasture performance. The methodology adopted was characterized by a bibliographical review of literature, which is based on pre-existing material to compose an analysis with the objective of highlighting, ratifying or rectifying any scientific gap in a given topic. In view of the above, it can be stated that forage plants adequately associated with mineral fertilization with NPK provide greater animal production. Considering that during periods of drought, pasture can be maintained if the production system has been correctly planned, thus enabling the maintenance of the animal's energy gain.